IMPLEMENTATION OF FISHBOWL LEARNING MODEL ON STUDENTS OF COMMUNICATION STUDENTS ON CONCEPT OF ENVIRONMENT POLLUTION IN CLASS X SMAN 18 TANGERANG REGENCY - Karina Ersanti; Aditya Rahman (Biodidaktika : Jurnal Biologi dan Pembelajarannya, 2017)
This research aimed to know the application and the influence of learning model fishbowl toward students communication ability to environmental pollution concept at SMAN 18 Kabupaten Tangerang. The method in this research is quasi experiment by research design randomized control group only. The sample were students of class X-3 as experiment class and X-4 as control class which were selected by random sampling. The collecting data using a written communication ability test, observation paper and. Analysis of hypothesis using U-Mann Whitney in the signification α=0.05. The result of the research obtained score signification is 0.000 < 0.05 for oral communication ability and written communication ability obtained score signification is 0.007< 0.05, can be conclude that the use learning model fishbowl influenced toward students communication ability to environmental pollution concept at SMAN 18 Kabupaten Tangerang both orally and in written. The analysis to observation result showed of criteria the student was interest used of learning model fishbowl with average score 69.9% in enough criteria.